Multilocus sequence typing of 102 Burkholderia pseudomallei strains isolated from China. Issue 9 (8th January 2016) - FANG, Y.; ZHU, P.; LI, Q.; CHEN, H.; LI, Y.; REN, C.; HU, Y.; TAN, Z.; GU, J.; MAO, X.
SUMMARY: The phylogenetic and epidemiological relationships of 102 Burkholderia pseudomallei clinical isolates from different geographical and population sources in China were investigated by multilocus sequence typing (MLST). The MLST data were analysed using the e-BURST algorithm, and an unweighted pair-group method with arithmetic mean dendrogram was constructed based on the pair-wise differences in the allelic profiles of the strains. Forty-one sequence types (STs) were identified, of which eight were novel (ST1341, ST1345, ST1346, ST1347, ST1348, ST1349, ST1350, ST1351). No geographical-specific or host population-specific phylogenetic lineages were identified. ST46, ST50, ST55, ST58, ST70 and ST1095 predominated, but ~44% of isolates were assigned to 45 STs illustrating high genetic diversity in the strain collection. Additionally, the phylogenetic relationships of the dominant STs in China showed significant linkeage with B. pseudomallei isolates from Thailand. Analysis of the gmhD allele suggests high genetic variation in B. pseudomallei in China.